Role of olfaction in host selection by Pseudaphycus maculipennis (Hymenoptera Encyrtidae) - Sandanayaka, W.R.M.; Charles, J.G.; Ramankutty, P. (New Zealand Plant Protection, 2005)
The volatile stimuli for host finding by Pseudaphycus maculipennis were examined in a Ytube olfactometer The responses of naïve female parasitoids (23 days old) to two mealybug species Pseudococcus viburni (obscure mealybug) and Pseudococcus longispinus (longtailed mealybug) on sprouting potato were measured The percentage of parasitoids to choose the odourladen arm compared to clean air was similar for both mealybug species on potato sprouts (80 to 825) When given a choice between mealybug species on potato sprouts the parasitoid preferred the obscure mealybug The parasitoids also responded to an excised sprout from an uninfested potato when compared with clean air Further choice tests showed that honeydew secreted by either mealybug species was similarly attractive while honeydew was more attractive than the ovisacs from obscure mealybug This work shows that P maculipennis exhibits a strong response to the plant of their host and prefer obscure mealybug to longtailed mealybug despite a similar response to honeydew from both species